The Hungry Eye : Eating, Drinking, and European Culture from Rome to the Renaissance - Barkan, Leonard (Book collections on Project MUSE., 2021)
"In discussions of arts and culture, food and drink are often relegated to the realms of mere decoration or mere necessity. However, like the term taste, which begins as one of the five senses but comes to be understood as the most sweeping term for human sensibility, eating and drinking can also be fundamental aesthetic experiences. In this book, author Leonard Barkan covers millennia of Western aesthetic and cultural activity, tracing the history of eating and drinking across literature, art, philosophy, statecraft, religion, and historiography. Drawing on a myriad of historical and analytic perspectives, Barkan demonstrates how the materials of the dining table, the flavor and pleasure of food, and hunger and satiety are central to life and culture. He explores what it means to "read for the food" in works of art, literature, and philosophy, and demonstrates the central role that food played in Roman civilization. He examines the deeply culinary qualities of the Hebrew Bible and the New Testament, the relationship between food and drink and the culture of the Renaissance, and the literal acts of consumption that are endowed with sacred significance. By uncovering the gastronomic underplot in cultural and artistic works, Barkan proposes an interdisciplinary approach to the relation between sense experience and aesthetic experience, and considers what it means to move from the margins to the center in a study of culture"--